Depresi: Ciri, Penyebab dan Penangannya - Aries Dirgayunita (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
Each person must have experienced a variety of problems and obstacles in his life. If someone in his life is hopeless and strength to face the problems of life, the person may experience depression can even become stressful. Depression is not only experienced by adults but children may also experience depression knows no social class. Many factors that cause a person to become depressed and down. Depression is one of the main causes of suicide (suicide). As many as 40% of patients with depression have suicidal ideas, and only approximately 15% that succeed do so. WHO predicts that by 2020, depression will be one of the more experienced of mental disorders and severe depression will be the second largest cause of death after a heart attack. Based on data from the WHO in 1980, nearly 20% - 30% of hospital patients in developing countries mental emotional disorder such as depression. Depression is an emotional disorder or a bad mood characterized by prolonged sadness, hopelessness, guilt and does not mean. So that all mental processes (thinking, feeling and behaving) can affect the motivation to move in daily life and in interpersonal relationships